Phenotypic characterization and documentation of animal genetic resources in India: A review - SINGH, P K; SHARMA, ARJAVA (The Indian Journal of Animal Sciences, 2016)
Phenotypic characterization is essential for planning and managing the animal genetic resources at local, national, regional and global levels. Large proportion of non-descript animals of different livestock species indicated that the characterization and inventorization of animal genetic resources of India is still incomplete. After establishment of National Bureau of Animal Genetic Resources (NBAGR) at Karnal by Indian Council of Agricultural Research (ICAR), phenotypic characterization of domestic animal diversity of India, accelerated. A large number of recognized livestock and poultry breeds and populations were systematically studied and documented in last three decades. A system of registration of livestock and poultry breeds was initiated by ICAR in India in 2008 with the registration of 129 livestock and poultry breeds. Thirty one new breeds were registered from 2010 to 2016. With the introduction these newly registered breeds, total number of indigenous breeds in the country now stands at 160, which include 40 breeds of cattle, 13 buffalo, 26 goat, 42 sheep, 6 horse and pony, 9 camel, 6 pig, 1 donkey and 17 of chicken. After registration of breeds, the breed descriptors were published in The Indian Journal of Animal Sciences. A large number of breed monographs were also published by different agencies. This review provides information of the breeds or population of livestock and poultry undertaken for phenotypic characterization and documentation in India.